PENGARUH KINERJA LINGKUNGAN, KINERJA KEUANGAN, DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Ersa Sabila Putri Pratama; Imam Ghozali (Diponegoro Journal of Accounting, 2022)
This study was conducted to investigate the effect of environmental performance, financial performance, and company characteristics on the disclosure of Corporate Social Responsibility (CSR). In this study, the characteristics of the companies tested include the size of the company and the age of the company. In addition, financial performance is measured by Return on Assets (ROA) and leverage.The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2019 – 2020. The sample selection used the purposive sampling method with the criteria and requirements determined by the researcher. The total research sample is 104 companies based on the criteria set by the researcher. This research uses multiple linear regression analysis method.The results showed that simultaneously all independent variables, namely environmental performance, Return on Assets (ROA), leverage, company size and company age had an effect on the disclosure of Corporate Social Responsibility (CSR). Partially, the results of the study show that environmental performance, company size, and company age have a significant positive influence on the disclosure of Corporate Social Responsibility (CSR). Return on Assets (ROA) has an insignificant positive effect on the disclosure of Corporate Social Responsibility (CSR), while leverage has an insignificant negative effect on the disclosure of Corporate Social Responsibility (CSR).